Synucleinopathies: Where we are and where we need to go. Issue 4 (19th February 2020) - Brás, Inês Caldeira; Dominguez‐Meijide, Antonio; Gerhardt, Ellen; Koss, David; Lázaro, Diana F.; Santos, Patrícia I.; Vasili, Eftychia; Xylaki, Mary; Outeiro, Tiago Fleming
Abstract: Synucleinopathies are a group of disorders characterized by the accumulation of inclusions rich in the a‐synuclein (aSyn) protein. This group of disorders includes Parkinson's disease, dementia with Lewy bodies (DLB), multiple systems atrophy, and pure autonomic failure (PAF). In addition, genetic alterations (point mutations and multiplications) in the gene encoding for aSyn ( SNCA ) are associated with familial forms of Parkinson's disease, the most common synucleinopathy. The Synuclein Meetings are a series that has been taking place every 2 years for about 12 years. The Synuclein Meetings bring together leading experts in the field of Synuclein and related human conditions with the goal of discussing and advancing the research. In 2019, the Synuclein meeting took place in Ofir, a city in the outskirts of Porto, Portugal. The meeting, entitled "Synuclein Meeting 2019: Where we are and where we need to go", brought together >300 scientists studying both clinical and molecular aspects of synucleinopathies. The meeting covered a many of the open questions in the field, in a format that prompted open discussions between the participants, and underscored the need for additional research that, hopefully, will lead to future therapies for a group of as of yet incurable disorders. Here, we provide a summary of the topics discussed in each session and highlight what we know, what we do not know, and what progress needs to be made in order to enable the field to continue to advance. We are confident this systematic assessment of where we stand will be useful to steer the field and contribute to filling knowledge gaps that may form the foundations for future therapeutic strategies, which is where we need to go. Abstract : This article is related to the Special Issue Synuclein which was solicited from the Synuclein Meeting 2019. Every 2 years for about 12 years, the Synuclein Meetings bring together leading experts in the field of Synuclein and related human conditions with the goal of discussing and advancing the research. Here, we provide a summary of the topics discussed in each session and highlight what we know, what we do not know, and what progress needs to be made in order to enable the field to continue to advance. Alpha‐synuclein (aSyn) is implicated in several neurodegenerative disorders of the brain and in this review we cover various aspects of aSyn biology and pathobiology, as depicted in the various circles. This article is related to the Special Issue "Synuclein"